Sexuality conceptions in adolescents with and without a sexual violence history - Rodrigues, Julliana Luiz; Brino, Rachel de Faria; Williams, Lúcia Cavalcanti Albuquerque (Paidéia (Ribeirão Preto), 2006)
The goals of this study consisted in verifying the sexuality conceptions of adolescents who have been victims of sexual violence compared to the ones who were not victims and to evaluate if both teenagers' groups (victims and not victims) differed regarding their scores in the Depression Inventory. The research was conducted with 16 female teenagers, eight youngsters victim of sexual violence, and eight nonvictims. In most victims' cases the aggressor was someone close to the victim and involved consummation of the vaginal sexual act. It was verified that the adolescents who experienced sexual violence, contrasting with the others, demonstrated striking fear regarding involvement with an individual of the opposite sex and also of the sexual act. In such group, mistaken ideas concerning sexuality were observed. Regarding feeling confortable in front of an individual of the opposite sex, all the abuse victims affirmed that they did not.